Implementación de un servidor web cache bajo la plataforma GNU/LINUX, automatizando scritps para óptiminizar el mantenimiento del servidor - Mora Andrade, Stephanie Elizabeth (2014)
In the present investigation we have implemented a web cache server maintenance by automating processes using scripts. The server works through a free operating system platform which is Debian 3.1.2 , which will be responsible Thundercache to cache web objects , to respond to new user requests. The re routing of requests to the server and not directly to the wan -a 750GL routerboard that was configured using the winbox for use in the network between the configurations we used . Among the tools we have used Putty which is the terminal commands used to manipulate Debian from another computer to the server , the Winscp used when access graphically server content . After the server implemented on the network operation will be efficient , the network users experience an improvement in performance of the same among which are: Reduce response times. If the web page you requested is in the cache server , it is served without logging back to the original server , thus saving time. Reduces network traffic and bandwidth consumption. If the web page is stored in the cache server , the request does not leave the local network and will not need to use the outside line and achieving savings in bandwidth utilization . The creation and automation scripts to allow us to provide a suitable server maintenance as this process is important for the proper functioning of the team. Another important factor of this research is to contribute to the learning of new technologies based on free platforms stressing save on software costs